Osseointegration of standard and mini dental implants: a histomorphometric comparison - Jagjit S. Dhaliwal; Rubens F. Albuquerque; Monzur Murshed; Jocelyne S. Feine (SpringerOpen, 2017)
Abstract Background Mini dental implants (MDIs) are becoming increasingly popular for rehabilitation of edentulous patients because of their several advantages. However, there is a lack of evidence on the osseointegration potential of the MDIs. The objective of the study was to histomorphometrically evaluate and compare bone apposition on the surface of MDIs and standard implants in a rabbit model. Methods Nine New Zealand white rabbits were used for the study to meet statistical criteria for adequate power. Total 18 3M™ESPE™ MDIs and 18 standard implants (Ankylos® Friadent, Dentsply) were inserted randomly into the tibia of rabbits (four implants per rabbit); animals were sacrificed after a 6-week healing period. The specimens were retrieved en bloc and preserved in 10% formaldehyde solution. Specimens were prepared for embedding in a light cure acrylic resin (Technovit 9100). The most central sagittal histological sections (30-40 μm thick) were obtained using a Leica SP 1600 saw microtome. After staining, the Leica DM2000 microscope was used, the images were captured using Olympus DP72 camera and associated software. Bone implant contact (BIC) was measured using Infinity Analyze software. Results All implants were osseointegrated. Histologic measures show mineralized bone matrix in intimate contact with the implant surface in both groups. The median BIC was 58.5 % (IQR 8.0) in the MDI group and 57.0 % (IQR 5.5) in the control group (P > 0.05; Mann-Whitney test). There were no statistical differences in osseointegration at 6 weeks between MDIs and standard implants in rabbit tibias. Conclusions Based on these results, it is concluded that osseointegration of MDIs is similar to that of standard implants.